Legal Review of Land Disputes Between Private Landowners and the Government in the Construction of a Community Health Center (Puskesmas) Based on Law Number 2 of 2012 (Case Study of Court Decision Number 52/Pdt.G/2023/PN Cjr) - Linda Ramadhayanti; Temmy Fitriah Alfiany (Dinasti Research, 2025)
This research examines a land dispute between a private landowner and the local government concerning the construction of a public facility without following lawful land acquisition procedures. The study focuses on Decision No. 52/Pdt.G/2023/PN Cjr issued by the Cianjur District Court, in which the Cianjur Regency Government built and operated the Muka Public Health Center (Puskesmas) on land owned by the plaintiff, without any process of land release, negotiation, or compensation. This study aims to analyze the legal provisions on land acquisition under Law No. 2 of 2012, the legal protection of private land rights, the legality of the Puskesmas construction, and the court’s legal reasoning. A normative legal research method was used, employing statutory and case approaches. The findings show that the development was unlawful, yet the court did not provide any concrete remedy to the landowner. The judgment acknowledged the unlawful act but did not order the demolition of the building or compensation by the government. This reveals a gap between legal recognition and substantive justice.